Association between transformational leadership, organizational commitments, and application of Total Quality Management (TQM) to employee performance in Sanglah General Hospital, Bali, Indonesia - Fery Dwiyanto; I Putu Ganda Wijaya; Putu Ayu Indrayathi (Intisari Sains Medis, 2020)
Background: Employee performance results from work achieved by an employee in quality and quantity in carrying out tasks in accordance with the responsibilities given. Good employee performance increases hospital customer satisfaction. This study aims to determine the relationship between transformational leadership, organizational commitment, and the application of Total Quality Management (TQM) with employee performance at Sanglah Central General Hospital.Methods: A cross-sectional study was conducted among 87 samples. Samples in each installation/unit that fulfilled inclusion criteria were selected using proportional random sampling. Data were analyzed using univariate, bivariate (chi-square), and multivariate (logistic regression) by SPSS version 20 for Windows.Results: Most employees perceived good in transformational leadership (67.8%), good organization commitment (55.2%), good application of TQM (75.9%), and good employee's performance (65.5%). The bivariate analysis shows a significant association between transformational leadership (p=0.001), organization commitment (p=0.001), and application of TQM (p=0.010) with employees' performance in Sanglah General Hospital. However, according to the multivariate analysis, a statistically significant association variable is organizational commitment (OR=547.96; 95% CI=4.922-613.673; p=0.001).Conclusion: Factors associated with the employee's performance in Sanglah Hospital are transformational leadership, organizational commitment, and TQM. Therefore, stakeholders in the hospital should consider the loyalty of employees in determining policies to improve service quality continuously.